Enabling urban climate resilience through integrated optimization of urban design - Feng, Wenhan; Yang, Liang Emlyn; Zeng, Fan; Jia, Jing; Zhang, Hengrui; Wu, Zheng (Frontiers in Sustainable Cities, 2025)
Rapid urbanization and climate change pose significant challenges to achieving sustainable and climate-adaptive urban development. This study develops an integrated evaluation framework that combines multi-indicator assessment, network analysis, and simulation to examine urban spatial typologies and identify optimization strategies. Applied to the city of Aachen, Germany, the framework reveals how key indicators such as energy use intensity, thermal comfort, and building density shape the trade-offs between environmental performance and spatial efficiency. Network analysis highlights leverage points where targeted interventions can generate cascading benefits across multiple domains, while simulation quantifies the impacts of alternative design strategies. The results show that compact typologies achieve higher spatial efficiency but often compromise daylight and thermal comfort, whereas open typologies perform better environmentally but underutilize land capacity. A hybrid typology demonstrates a more balanced performance, suggesting pathways for reconciling density with comfort and efficiency. Beyond technical outcomes, the study underscores the role of urban design as a governance mechanism: by embedding cross-sectoral performance requirements into the design process, it can enhance coordination, reduce institutional fragmentation, and support more coherent climate governance. The findings provide planners with actionable insights and methodological tools to balance multiple objectives and advance climate resilience in diverse urban contexts.